2021
DOI: 10.1093/esr/jcab015
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Class Attainment and Social Mobility: An Analysis of Migrants’ Socio-Economic Integration in Italy

Abstract: This article focuses on the socio-economic integration of ethnic minorities in Italy, combining the literature on migration with research on social stratification. We analyse the ethnic penalty on occupational attainment and career mobility, integrating the origin–education–destination theoretical framework with the migration status. Since ethnic penalty is an ‘umbrella concept’, we also quantify the extent to which it is mediated by differences in education and social origin. Furthermore, adopting a diachroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…This allows to highlight the importance of both education and social origin as important drivers of migrants' socio-economic integration, as well as how this interrelation changes over countries. This issue -which has been rarely addressed in comparative studies -is central in the most recent research on second-generation migrants (Gracia, Vázquez-Quesada, and Van de Werfhorst, 2016;Heath, Rothon, and Kilpi, 2008;Platt, 2005aPlatt, ,2005bZuccotti, 2015;Zuccotti and Platt, 2021;Zwysen and Longhi, 2018), whereas few studies analyzed this issue considering the first-generation migrants (Avola and Piccitto, 2020;Panichella et al, 2021;Li and Heath, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This allows to highlight the importance of both education and social origin as important drivers of migrants' socio-economic integration, as well as how this interrelation changes over countries. This issue -which has been rarely addressed in comparative studies -is central in the most recent research on second-generation migrants (Gracia, Vázquez-Quesada, and Van de Werfhorst, 2016;Heath, Rothon, and Kilpi, 2008;Platt, 2005aPlatt, ,2005bZuccotti, 2015;Zuccotti and Platt, 2021;Zwysen and Longhi, 2018), whereas few studies analyzed this issue considering the first-generation migrants (Avola and Piccitto, 2020;Panichella et al, 2021;Li and Heath, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research showed that the effect of education and social origin interact with the migration status (Zuccotti, 2015), since several mechanisms of reproduc-tion of social inequality are 'country-specific' (Torche, 2015), i.e. they cannot be transferred among societies (Panichella et al, 2021). However, it is not yet clear how these mechanisms change among different European receiving countries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations